Pendidikan Inklusi dengan Anak Penyandang Ketunaan Slow Learner (Lambat Belajar) dan CIBI (Cerdas Istimewa, Berbakat Istimewa) - Nurfadhillah, Septy; Fitri, Aisah Nur; Utami, Dyah; Navyanti, Faradya; J, Ghina Salsabila; Ustianingsih, Laysia; Izzah, Nurul; Amalia, Reny Rahma (ALSYS, 2022)
This research was conducted at SDN Cimone 7, Tangerang City, Banten Province. This research was conducted aiming to find out and then understand the inclusive school environment which in practice is not only the interaction between teachers and students as the primary component of education, but also the presence of supporting facilities such as school facilities and infrastructure that are the foundation of the smooth process of school formal education. This study uses the method of observation and the instrument used is in the form of interviews. The results of this observational study indicate (1) there are inclusive schools located in the Tangerang City area, (2) there are inclusive students at SDN Cimone 7, Tangerang City, Banten Province which are classified as slow learners .and special intelligent and gifted children (CIBI), (3) knowledge of the learning system implemented at SDN Cimone 7 Tangerang City, Banten Province. Based on the results of the research that has been done, it can be seen that SDN Cimone 7 Tangerang City, Banten Province is included in an inclusive school that has tried to implement a learning system that adapts to the needs of these inclusive students.